The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/jcs7060240
|View full text |Cite
|
Sign up to set email alerts
|

Conducting Polymer Nanocomposites for Electromagnetic Interference Shielding—Radical Developments

Abstract: Electromagnetic interference disturbs the working of electronic devices and affects the surroundings and human health. Consequently, research has led to the development of radiation-protection materials. Inherently conducting polymers have been found to be suitable for electromagnetic interference (EMI) shielding owing to their fine electrical conductivity properties. Moreover, nanoparticle-reinforced conjugated polymers have been used to form efficient nanocomposites for EMI shielding. Nanoparticle addition h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 135 publications
0
1
0
Order By: Relevance
“…It has been found that carbon nanotubes have been employed in super-capacitor electrodes and the CNT-based nanocomposites have mechanical resistance, desirable structure, and high surface area [28,34]. Meanwhile, CNT-based composites show efficient electromagnetic-interference-shielding capacity due to their high magnetism, electrical conductivity, aspect ratio, real/imaginary permittivity, and interfacial polarization [35,36]. Moreover, carbon nanotubes offer excellent electron affinity and transportation performance in some special polymers, which can be applied in bulk to heterojunction solar cells [28].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that carbon nanotubes have been employed in super-capacitor electrodes and the CNT-based nanocomposites have mechanical resistance, desirable structure, and high surface area [28,34]. Meanwhile, CNT-based composites show efficient electromagnetic-interference-shielding capacity due to their high magnetism, electrical conductivity, aspect ratio, real/imaginary permittivity, and interfacial polarization [35,36]. Moreover, carbon nanotubes offer excellent electron affinity and transportation performance in some special polymers, which can be applied in bulk to heterojunction solar cells [28].…”
Section: Introductionmentioning
confidence: 99%